1996
DOI: 10.1128/mcb.16.5.2325
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among SR Proteins, an Exonic Splicing Enhancer, and a Lentivirus Rev Protein Regulate Alternative Splicing

Abstract: We examine here the roles of cellular splicing factors and virus regulatory proteins in coordinately regulating alternative splicing of the tat/rev mRNA of equine infectious anemia virus (EIAV). This bicistronic mRNA contains four exons; exons 1 and 2 encode Tat, and exons 3 and 4 encode Rev. In the absence of Rev expression, the four-exon mRNA is synthesized exclusively, but when Rev is expressed, exon 3 is skipped to produce an mRNA that contains only exons 1, 2, and 4. We identify a purine-rich exonic splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 52 publications
4
58
0
Order By: Relevance
“…Compared with the consensuses obtained with 9G8, 9G8Zn m (this study), and ASF/SF2 (Tacke & Manley, 1995), results obtained with SC35 are more unexpected+ We identified a panel of five different consensuses that are partially related (see Fig+ 3), the two most divergent consensuses being comparable to those identified previously (Tacke & Manley, 1995)+ However, all tested SC35 binding sequences containing one or two copies of these consensuses are efficiently recognized by the recombinant SC35 or endogenous SC35 in the nuclear extract (Figs+ 5 and 6), thus validating our SELEX selection and indicating that the identified consensuses are all bona fide SC35-specific targets+ In contrast to results obtained with other SRp30-specific targets, we have shown that the SC35-specific targets are unable to activate efficient in cis splicing within the two first model substrates tested, although two of five activate moderately splicing of the E1A-derived substrate in highly favorable splicing conditions (Fig+ 8C)+ Furthermore, duplication of a SC35-specific target in the last model substrate did not result in splicing activation (data not shown)+ It seems unlikely that the absence or weakness of splicing activation results from a problem of accessibility of the SC35 sequences because they were inserted in the substrates in the same context as the other specific targets+ Thus, we conclude that SC35 cannot activate splicing of a substrate containing a weak 39 splice site and a single or double high-affinity target as efficiently as other SR proteins, in agreement with previous results from Tacke & Manley (1995)+ In fact, no clear example of natural enhancer activation by SC35 has been reported, whereas several examples of activation by ASF/SF2 have been described (Sun et al+, 1993;Ramchatesingh et al+, 1995;Gontarek & Derse, 1996;Lynch & Maniatis, 1996; Gallego et al+, 1997)+ Moreover, SC35 even exhibits an antagonistic effect on ASF/SF2-activated splicing of the b-tropomyosin exon 6A, which depends on an intronic enhancer (Gallego et al+, 1997)+ These results do not exclude, however, that SC35 might play an active role in transactivation, through cooperation with other SR proteins or splicing coactivators+ Clearly, the in vitro approach including the selection for high-affinity targets for one SR species (the "binding SELEX") followed by the assessment of these targets as specific splicing enhancers leads to the identification of well-defined consensus for ASF/SF2 (Tacke & Manley, 1995), SRp40 (Tacke et al+, 1997), as well as 9G8, 9G8Zn m , and SRp20, but not SC35 (this study)+ Another approach has been described recently by Liu et al+ (1998) for identifying functional splicing enhancers for ASF/SF2, SRp40, and SRp55 and has been defined as "functional SELEX" by these authors+ However, employing this technique with ASF/SF2 and SRp40 resulted in more degenerate RNA sequences, which were different from the sequences previously identified (Tacke & Manley, 1995;…”
Section: Sc35 Is Not Able To Transactivate Splicing Through Its Specisupporting
confidence: 79%
“…Compared with the consensuses obtained with 9G8, 9G8Zn m (this study), and ASF/SF2 (Tacke & Manley, 1995), results obtained with SC35 are more unexpected+ We identified a panel of five different consensuses that are partially related (see Fig+ 3), the two most divergent consensuses being comparable to those identified previously (Tacke & Manley, 1995)+ However, all tested SC35 binding sequences containing one or two copies of these consensuses are efficiently recognized by the recombinant SC35 or endogenous SC35 in the nuclear extract (Figs+ 5 and 6), thus validating our SELEX selection and indicating that the identified consensuses are all bona fide SC35-specific targets+ In contrast to results obtained with other SRp30-specific targets, we have shown that the SC35-specific targets are unable to activate efficient in cis splicing within the two first model substrates tested, although two of five activate moderately splicing of the E1A-derived substrate in highly favorable splicing conditions (Fig+ 8C)+ Furthermore, duplication of a SC35-specific target in the last model substrate did not result in splicing activation (data not shown)+ It seems unlikely that the absence or weakness of splicing activation results from a problem of accessibility of the SC35 sequences because they were inserted in the substrates in the same context as the other specific targets+ Thus, we conclude that SC35 cannot activate splicing of a substrate containing a weak 39 splice site and a single or double high-affinity target as efficiently as other SR proteins, in agreement with previous results from Tacke & Manley (1995)+ In fact, no clear example of natural enhancer activation by SC35 has been reported, whereas several examples of activation by ASF/SF2 have been described (Sun et al+, 1993;Ramchatesingh et al+, 1995;Gontarek & Derse, 1996;Lynch & Maniatis, 1996; Gallego et al+, 1997)+ Moreover, SC35 even exhibits an antagonistic effect on ASF/SF2-activated splicing of the b-tropomyosin exon 6A, which depends on an intronic enhancer (Gallego et al+, 1997)+ These results do not exclude, however, that SC35 might play an active role in transactivation, through cooperation with other SR proteins or splicing coactivators+ Clearly, the in vitro approach including the selection for high-affinity targets for one SR species (the "binding SELEX") followed by the assessment of these targets as specific splicing enhancers leads to the identification of well-defined consensus for ASF/SF2 (Tacke & Manley, 1995), SRp40 (Tacke et al+, 1997), as well as 9G8, 9G8Zn m , and SRp20, but not SC35 (this study)+ Another approach has been described recently by Liu et al+ (1998) for identifying functional splicing enhancers for ASF/SF2, SRp40, and SRp55 and has been defined as "functional SELEX" by these authors+ However, employing this technique with ASF/SF2 and SRp40 resulted in more degenerate RNA sequences, which were different from the sequences previously identified (Tacke & Manley, 1995;…”
Section: Sc35 Is Not Able To Transactivate Splicing Through Its Specisupporting
confidence: 79%
“…A second example involves the equine infectious anemia virus, which contains an exonic enhancer element in a bicistronic mRNA encoding Tat and Rev. This exonic enhancer has also been shown to interact with SF2͞ASF (47). Rev binding to this exonic enhancer results in exon skipping and the induction of an mRNA encoding Tat only (47).…”
Section: Discussionmentioning
confidence: 99%
“…This exonic enhancer has also been shown to interact with SF2͞ASF (47). Rev binding to this exonic enhancer results in exon skipping and the induction of an mRNA encoding Tat only (47). The adenovirus L1 transcription unit is a third example of an alternatively spliced pre-mRNA that contains one 5Ј splice site that can be joined to one of two different 3Ј splice sites to produce either 52,55K or IIIa mRNAs (48).…”
Section: Discussionmentioning
confidence: 99%
“…Splicing enhancer sequences have been identified in several regulated and constitutive exons, and may be classified into purine rich (40) and nonpurine rich (41). Enhancers interact with SR proteins, including SF2/ASF (35,(42)(43)(44)(45)(46)(47)(48). SF2/ASF has high binding affinity for certain purinerich sequences in vitro (49) and, under splicing conditions, SF2/ASF and SC35 function through distinct and degenerate consensus sequences (50 -52).…”
Section: Discussionmentioning
confidence: 99%